Hai Maut Dimanakah Sengatmu? Eksposisi 1 Korintus 15:54-55 dan Maknanya Bagi Kehidupan Jemaat Masa Kini - Darmadi, Daud (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
This research analyzes the theological meaning of the quotations from Isaiah 25:8 and Hosea 13:14 in 1 Corinthians 15:54-55, as well as the hermeneutical transformation undertaken by Paul to affirm Christ's victory over sin and death. The method employed is exegetical hermeneutics based on G.K. Beale's model with comparative intertextual analysis between Old Testament texts and their application in the New Testament context. The analysis reveals that Isaiah 25:8 proclaims the eschatological abolition of death within the context of Israel's restoration, while Hosea 13:14 articulates death's powerlessness in the face of God's sovereignty. Paul conducts a Christological reinterpretation by transforming both quotations into a declaration of soteriological victory, wherein Christ's resurrection is understood as an eschatological fulfillment that definitively defeats the power of sin and death. Christ's resurrection in Paul's perspective functions as an eschatological proclamation of victory that transforms the lives of believers. These findings confirm that Paul's hermeneutics transforms the theological meaning of Old Testament texts within a Christological framework to provide doctrinal foundation for the early Christian community.